Lafora Disease Presenting with Ataxia and DM1: A Case Study - Ramin Khanalizadeh; Kosar Karimi (Acta Neurologica Taiwanica)
Here we presented a rare case of Lafora disease with neuropathy, ataxia and progression of symptoms into type one DM, GTCS and myoclonus during years. We believe that it is important to keep the diagnosis of Lafora disease in mind in every child presenting with myoclonus especially when mental and cerebellar deficits develop as well.